Distribution of sediment bacterial and archaeal communities in plateau freshwater lakes - Zhang, Jingxu; Yang, Yuyin; Zhao, Lei; Li, Yuzhao; Xie, Shuguang; Yong Liu (APPLIED MICROBIOLOGY AND BIOTECHNOLOGY, 2015)
Both Bacteria and Archaea might be involved in various biogeochemical processes in lacustrine sediment ecosystems. However, the factors governing the intra-lake distribution of sediment bacterial and archaeal communities in various freshwater lakes remain unclear. The present study investigated the sediment bacterial and archaeal communities in 13 freshwater lakes on the Yunnan Plateau. Quantitative PCR assay showed a large variation in bacterial and archaeal abundances. Illumina MiSeq sequencing illustrated high bacterial and archaeal diversities. Bacterial abundance was regulated by sediment total organic carbon and total nitrogen, and water depth, while nitrate nitrogen was an important determinant of bacterial diversity. Proteobacteria, Acidobacteria, Actinobacteria, Bacteroidetes, Chlorobi, Chloroflexi, Cyanobacteria, Firmicutes, Gemmatimonadetes, Nitrospirae, Planctomycetes, and Verrucomicrobia were the major components of sediment bacterial communities. Proteobacteria was the largest phylum, but its major classes and their proportions varied greatly among different lakes, affected by sediment nitrate nitrogen. In addition, both Euryarchaeota and Crenarchaeota were important members in sediment archaeal communities, while unclassified Archaea usually showed the dominance.